POTENTIAL OF Bacillus spp. ANTAGONISTS FOR SUPPRESSION OF Xanthomonas euvesicatoria PHYTOPATHOGENS - Pajčin, Ivana; Vlajkov, Vanja; Rončević, Zorana; Dodić, Jelena; Grahovac, Mila; Ignjatov, Maja; Grahovac, Jovana (Journal on Processing and Energy in Agriculture, 2020)
Bacterial pathogens Xanthomonas euvesicatoria, principal causers of bacterial spot, represent significant problem in agricultural practice due to high yield losses in production of pepper and tomato. Development of resistance to copper pesticides has shifted research in the field of their suppression towards biopesticides. In this study, several Bacillus strains were tested to select antagonist sufficiently effective against Xanthomonas euvesicatoria strains, isolated from pepper leaves with symptoms of bacterial spot. When it comes to testing of cultivation broth, containing biomass of tested antagonists, the best results were achieved using isolate Bacillus sp3. On the other hand, when biomass-free supernatants, containing produced antimicrobial compounds, were tested, Bacillus sp1 and Bacillus sp2 have showed the highest antimicrobial activity. The results of this study represent a basis for further development of bioprocess solutions for production of biopesticides based on Bacillus spp. biomass or antimicrobial compounds, showing high efficiency in suppression of pepper bacterial spot.
Keywords: antimicrobial activity; pepper; bacterial spot; biomass; antimicrobial compounds; sensitivity